(untitled) - Pusins, Dolores Wells; Dolores Wells-Pusins; Ann Ambrose (Australia,Cambridge, MA, 2001)
Offering a basic introduction to computers, this text covers computer hardware, software, input, applications skills, the Internet and Web page creation, careers, computer ethics and more. Step-by-step instructions along with numerous screen shots and illustrations help readers learn and master essential computer concepts and skills
Keywords: Computers